Evaluation of the Active Support and Yielding Bearing Properties of Artificial Pillars Supporting a Stope Roof Using 3DEC Numerical Simulation - Kunmeng Li; Yuanhui Li; Hongdi Jing (Advances in Civil Engineering)
Before achieving yielding support with artificial pillars, it is significant to evaluate their active support and passive bearing performances on the stope roof. This paper focuses on three aspects of research using 3DEC numerical simulation, which are support patterns of artificial pillars, magnitude of support stresses, and the magnitude of prestresses of the load-increasing yielding support pattern. Simulation results show that the superior sequence of supporting effect is load-increasing yielding support, load-shedding yielding support, and constant and nonyielding support under the same initial support stress. When the magnitude of support stress or the magnitude of prestress is larger with load-increasing yielding support, the supporting effect is superior and the load-increasing yielding support with a lower magnitude of support stress is superior to some other support patterns with higher magnitude of support stresses. The active support can improve the support effect compared with no prestress, and under the same final support stress, the support effect is superior when the roof stress releases more in the early supporting stage regardless of the prestress.